A simplified table using validated diagnostic criteria is effective to improve characterization of colorectal polyps: the CONECCT teaching program - Fabritius, Martin; Gonzalez, Jean-Michel; Becq, Aymeric; Dray, Xavier; Coron, Emmanuel; Brenet-Defour, Lucie; Branche, Julien; Gerard, Romain; Lepage, Côme; Poincloux, Laurent; Lienhart, Isabelle; Bonniaud, Paul; Bounnah, Mohamed Tayeb; Rivory, Jérôme; Lépilliez, Vincent; Subtil, Fabien; Saurin, Jean-Christophe; Ponchon, Thierry; Jacques, Jérémie; Pioche, Mathieu (Endoscopy International Open, 2019)
Introduction and study aims Accurate real-time endoscopic characterization of colorectal polyps is key to choosing the most appropriate treatment. Mastering the currently available classifications is challenging. We used validated criteria for these classifications to create a single table, named CONECCT, and evaluated the impact of a teaching program based on this tool.Methods A prospective multicenter study involving GI fellows and attending physicians was conducted. During the first session, each trainee completed a pretest consisting in histological prediction and choice of treatment of 20 colorectal polyps still frames. This was followed by a 30-minute course on the CONECCT table, before taking a post-test using the same still frames reshuffled. During a second session at 3 – 6 months, a last test (T3 M) was performed, including these same still frames and 20 new ones.Results A total 419 participants followed the teaching program between April 2017 and April 2018. The mean proportion of correctly predicted/treated lesions improved significantly from pretest to post-test and to T3 M, from 51.0 % to 74.0 % and to 66.6 % respectively (P < 0.001). Between pretest and post-test, 343 (86.6 %) trainees improved, and 153 (75.4 %) at T3 M. Significant improvement occurred for each subtype of polyp for fellows and attending physicians. Between the two sessions, trainees continued to progress in the histology prediction and treatment choice of polyps CONECCT IIA. Over-treatment decreased significantly from 30.1 % to 15.5 % at post-test and to 18.5 % at T3 M (P < 0.001). Conclusion The CONECCT teaching program is effective to improve the histology prediction and the treatment choice by gastroenterologists, for each subtype of colorectal polyp.